DIAGNOSIS DAN TATALAKSANA RENAL TUBULAR ASIDOSIS TIPE 1 PADA PASIEN DENGAN LUPUS ERITEMATOSUS SISTEMIK - Elim Jusri; Yenny Kandarini; Gede Wira Mahadita (Al-Iqra Medical Journal : Jurnal Berkala Ilmiah Kedokteran, 2023)
Systemic lupus erythematosus (SLE) is an autoimmune disease affecting several body systems with a variety of clinical manifestations, course of disease, and prognosis. Its clinical manifestations can involve almost all organ systems including musculoskeletal, skin and mucosa, kidney, neuropsychiatry, lung, heart, blood vessels, gastrointestinal, ocular, obstetric, endocrine, and haematology. SLE can occur with a variety of degrees of tubular abnormalities. Tubular inflammation, tubular atrophy, interstitial inflammation and fibrosis are reported in 50-70% of patients with SLE. We have reported a case of a 27-year-old female with renal tubular acidosis (RTA) type 1 who has systemic lupus erythematosus. RTA is a group of abnormalities of the renal function, characterized by renal impairment in the reabsorption of HCO3- and excreting acid (H+). The administration of corticosteroids and immunosuppressants, correction of metabolic acidosis with sodium bicarbonate, and potassium supplementation are the main modalities of therapy in patients with SLE with RTA type-1